The Effect of Recruitment, Selection, and Job Placement on Employee Performance of PT. XYZ - Sri Zuliarni; Mestika Juniwan Nazara (West Science Business and Management, 2025)
The purpose of this study is to analyze the determinants of selection, recruitment, and job placement to the performance of PT. XYZ employees. The study used quantitative methods by distributing questionnaires to 118 respondents from the population of security employees. The results of the analysis show that Recruitment, selection and placement of employees at the simultaneous level provide positive determinant significance on employee performance whose F-count value is 42.240> F-table 3.076 and also the significance score is 0.000 <0.05, recruitment has a t-count score of 2.603><t-table 1.981 or a significance score of 0.010<0.05, selection has a t-count score of 2.485t-table 1.981 or a significance score of 0.014 <0.05, and job placement has a t-count score of 4.564 > 1-table of 1.981 or a significance score of 0.000 0.05. This study concludes that the performance of PT. XYZ employees has a positive determinant significance both at partial and simultaneous levels by recruitment, selection and job placement.